The correspondence of Wolfgang Capito. - Capito, Wolfgang, 1478-1541 (University of Toronto Press, 2009)
This volume continues in the tradition of rigorous scholarship established by the first, providing crucial details on the evolution of Capito's thought to Reformation scholars.